Exploring correlation between characteristics of board of directors and audit fees: the case of oil and gas industry. - Guo, Chengnian (2022)
Both the board of directors and the accounting firm exist on the basis of a fiduciary duty to address agency issues. What is the relationship between the two as a means of monitoring management? The audit fees paid by a listed company to an accounting firm are influenced by a number of factors, such as the size of the company being audited and audit risk. The board of directors of a listed company is one of the key internal factors in corporate governance. Therefore, the following three hypotheses are proposed: (1) There is a positive relationship between the size of the board of directors and audit fees. (2) There is a positive correlation between the proportion of independent directors on the board and audit fees. (3) There is a positive relationship between the proportion of women on the board of directors and audit fees. A sample of 99 oil and gas companies listed on the London Stock Exchange in the UK from 2018 to 2020 is selected for the empirical study. Board size, the proportion of independent directors on the board and the proportion of women on the board are used as variables to describe board characteristics. The Simunic (1980) model is used as the basis and then modified from there. The main findings of this study: board size and audit fees are significantly and positively related. When the board size is larger, audit fees are higher. The proportion of independent directors on the board and audit fees are significantly and positively related. When the number of independent directors on the board is higher, audit fees are higher. The proportion of women on the board and audit fees are significantly and positively related. When the number of female members on the board is higher, audit fees are higher.